-2(5z+3)=-11z

Simple and best practice solution for -2(5z+3)=-11z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(5z+3)=-11z equation:


Simplifying
-2(5z + 3) = -11z

Reorder the terms:
-2(3 + 5z) = -11z
(3 * -2 + 5z * -2) = -11z
(-6 + -10z) = -11z

Solving
-6 + -10z = -11z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '11z' to each side of the equation.
-6 + -10z + 11z = -11z + 11z

Combine like terms: -10z + 11z = 1z
-6 + 1z = -11z + 11z

Combine like terms: -11z + 11z = 0
-6 + 1z = 0

Add '6' to each side of the equation.
-6 + 6 + 1z = 0 + 6

Combine like terms: -6 + 6 = 0
0 + 1z = 0 + 6
1z = 0 + 6

Combine like terms: 0 + 6 = 6
1z = 6

Divide each side by '1'.
z = 6

Simplifying
z = 6

See similar equations:

| 5x+3x=5-3 | | -20+2c=-7(3c+20)+15c | | x+27=37 | | 5t+6=3t+14 | | 2senx-1-cosx=0 | | -4(-6)+5= | | 2n+5n=0 | | 5k+13+5k=8k-19 | | 2g+6(5g-16)=5+19+20g | | 13/20x-15 | | 2senx-1+cosx=0 | | -5+p=9+3p | | 1/2(5x-8)=-9 | | 5m+4m=9 | | 15+15p=-9(-3p+13) | | -6h+5=-10-7h+9 | | -2(20h-18)-20h=3(-h-7) | | g=(x+7)(x+3) | | -12r+6(-16r-5)=-6(19r+19) | | 2(3x+4)=3(6x-5) | | 9+7j=4j | | X+5-2x=3+x | | x=2000000+0.333y | | 2x-24=82 | | -7-3n=-5n | | -7-2r=4+9r | | 2+4*5=30 | | -8=-3n+5n | | -6(-m-8)=-10m | | (2x-1)/3=(5x-6)/4 | | -10-7q=10-9q | | 11n-9=5n+45 |

Equations solver categories